ARAPÇA İÇİN ULUSLARARASI STANDART BİR SINAV GELİŞTİRME MODELİ. - EKİNCİ, İsmail (Dinbilimleri Journal)
This article addresses a model for developing a standardized language proficiency exam for Arabic that possesses international validity, reliability, and comparability. The study aims to adapt global reference frameworks such as the Common European Framework of Reference for Languages (CEFR) and the American Council on the Teaching of Foreign Languages (ACTFL) to Arabic, taking into account the language’s unique linguistic features, including diglossia, root-and-pattern morphology, and an unvocalized writing system. The proposed model evaluates the four core skills (listening, reading, speaking, writing) based on Modern Standard Arabic (MSA) with balanced and scientific criteria, while integrating advanced psychometric methods (Item Response Theory - IRT, Computerized Adaptive Testing - CAT) and AI-supported hybrid scoring systems. Additionally, principles of cultural neutrality, fairness, and digital sustainability are observed in the exam, and a comprehensive implementation plan supported by a multinational consortium and continuous improvement mechanisms is presented. This model aims to contribute to positioning Arabic as a valid and reliable means of communication at international standards in both academic and professional contexts.